Cortical riders of zonular cataracts as "reverse cuneiform" cataracts: A hypothesis. (December 2018) - Khokhar, Sudarshan; Gupta, Yogita; Dhull, Chirakshi; Surve, Abhidnya; Mahabir, Manish
Abstract: Zonular cataracts are childhood cataracts involving one or more zone(s) of lens. They often show 'riders' which are wedge-shaped opacifications of inner cortex of the lens seen to radiate towards the lens equator, though little is known about the exact mechanism behind their development. Cortical riders may be described as 'reverse cuneiform' cataracts on the basis of their evolution pattern being exact opposite to that of senile cuneiform cortical cataracts.